Understanding the Concept of Different Stochastic Inventory Models: A Comprehensive Study on Stochastic Inventory Models and Their Application (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper displays a mathematical model for an inventory control system in which customers' demands and providers' service time are considered as stochastic parameters. Various aspects related to inventory theory are discussed in this article. A concise survey on stochastic process and stochastic inventory model is given for better understanding. We are taken two model, In the principal model we analyse a (s, S) generation Inventory system and in the model-II we stretch out these outcomes to perishable inventory system assuming that the life-time of each item pursues exponential distribution with parameter θ. There are several basic considerations engaged with deciding an inventory approach that must be reflected in the mathematical inventory model.